Physical activity intervention promotes working memory and motor competence in preschool children - Zhang, Jing-Yi; Shen, Qi-Qi; Wang, Dong-Ling; Hou, Jin-Mei; Xia, Tong; Qiu, Shou; Wang, Xiao-Ye; Zhou, Si-Bo; Yang, Wen-Wen; Heng, Si-Yu; Lu, Can-Can; Cui, Lei; et al. (Frontiers in Public Health, 2022)
Objective This study investigated the effects of 12 weeks of specifically designed physical activity intervention on working memory and motor competence in preschool children and explored the correlation between working memory changes and motor competence changes by the intervention. Methods Four classes of preschool children were grouped into an intervention group and a control group. Children in the intervention group received a 12-week physical activity intervention, while children in the control group followed their daily routine as usual. Before and after the intervention period, children were assessed with the 1-back task and Movement Assessment Battery for Children, second edition (MABC-2) to measure their working memory and motor competence, respectively. Results Regarding working memory, the accuracy on the 1-back task increased significantly in the intervention group relative to the control group. The intervention group demonstrated a greater decrease in response time from pre- to posttest than the control group, but the difference was not statistically significant. Regarding motor competence, children's manual dexterity, aiming and catching and total score increased significantly in the intervention group relative to the control group, while no significant difference in static and dynamic balance was observed between the two groups. Furthermore, the correlation results showed that changes in the efficacy and efficiency of working memory were positively related to changes in static and dynamic balance and the total score on the MABC-2. Conclusion These findings demonstrated that 12 weeks of specifically designed physical activity intervention could improve preschool children's efficacy of working memory as well as manual dexterity, aiming and catching and global motor competence. The improvement in the efficacy and efficiency of working memory was positively related to the improvement in static and dynamic balance and global motor competence.